ESCRT‐mediated lysosome repair precedes lysophagy and promotes cell survival. (12th October 2018) - Radulovic, Maja; Schink, Kay O; Wenzel, Eva M; Nähse, Viola; Bongiovanni, Antonino; Lafont, Frank; Stenmark, Harald
Abstract: Although lysosomes perform a number of essential cellular functions, damaged lysosomes represent a potential hazard to the cell. Such lysosomes are therefore engulfed by autophagic membranes in the process known as lysophagy, which is initiated by recognition of luminal glycoprotein domains by cytosolic lectins such as Galectin‐3. Here, we show that, under various conditions that cause injury to the lysosome membrane, components of the endosomal sorting complex required for transport (ESCRT)‐I, ESCRT‐II, and ESCRT‐III are recruited. This recruitment occurs before that of Galectin‐3 and the lysophagy machinery. Subunits of the ESCRT‐III complex show a particularly prominent recruitment, which depends on the ESCRT‐I component TSG101 and the TSG101‐ and ESCRT‐III‐binding protein ALIX. Interference with ESCRT recruitment abolishes lysosome repair and causes otherwise reversible lysosome damage to become cell lethal. Vacuoles containing the intracellular pathogen Coxiella burnetii show reversible ESCRT recruitment, and interference with this recruitment reduces intravacuolar bacterial replication. We conclude that the cell is equipped with an endogenous mechanism for lysosome repair which protects against lysosomal damage‐induced cell death but which also provides a potential advantage for intracellular pathogens. Synopsis: Damaged lysosomes are lethal to cells and cleared by lysophagy. While pathways exist to protect lysosomes from damage, repair mechanisms for injured organelles are unknown. Here ESCRT proteins, originally identified as regulators of protein sorting, are shown to promote the repair of lysosomal membrane and bacteria‐containing vacuoles to protect cells against cell death and provide replicative advantage to pathogens, respectively. ESCRT‐I, ‐II and ‐III proteins are recruited to damaged endolysosomal membranes. The ESCRT machinery mediates repair of damaged lysosomes. ESCRT recruitment to damaged lysosomes precedes lysophagy. ESCRT‐mediated lysosome repair promotes cell viability after lysosome injury. ESCRT recruitment to Coxiella burnetii vacuoles promotes bacterial replication. Abstract : ESCRT proteins, components of the protein sorting machinery, promote repair of damaged lysosomes and vacuoles. Lysosomal repair protects cells from cell death, while vacuolar repair provides a replicative advantage to certain pathogens.